Resistensi Bibit Kelapa Sawit dengan Perlakuan Trichoderma Sp., Mikoriza, dan Pupuk Kcl terhadap InfeksiInokulum Ganoderma Boninese - Wahyuni, Mardiana; Yosephine, Ingrid Ovie (Universitas Medan Area, 2020)
Root rot disease caused by the Ganoderma boninense fungus is a serious problem in oil palm cultivation. Initially this disease attacks mature plants, plants of the 3rd generation; but at this time Ganoderma disease has attacked immature plants and nurseries. Ganodermapathogens are soil borne. Improvement of growing conditions needs to be improved with the application of chemical fertilizers and the use of biological agents such as Trichoderma and Mycorrhizae. This study aims to determine the resistance of oil palm seeds with KCl, Trichoderma, and Mycorrhizal fertilizer treatments. The Ganoderma inoculum is infused in the form of a Rubber Wood Block (RWB). The research design was a factorial randomized block design consisting of 3 treatments, namely Trichoderma (T0, T1,T2), Mycorrhizae (M0, M1, M2), and KCl fertilizer (K0, K1, K2). There were 18 treatments with 3 replications. Observation parameters were seed height, number of leaves, roots, and attack intensity. The growth of seedlings at the 3rd and 5th months showed that the growth of seedlings was due to Ganoderma infection. Trichoderma and mycorrhizal treatment increased the number of healthy roots and crown dry weight. The treatment of KCl fertilizer only plays a role in root health. The best treatment is T1M2K1.Keywords: